2010
DOI: 10.2174/157339910793360842
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab (Avastin®) for Diabetic Retinopathy at 24-months: The 2008 Juan Verdaguer-Planas Lecture

Abstract: Diabetic retinopathy (DR) remains the major threat to sight in the working age population. Diabetic macular edema (DME) is a manifestation of DR that produces loss of central vision. Proliferative diabetic retinopathy (PDR) is a major cause of visual loss in diabetic patients. In PDR, the growth of new vessels is thought to occur as a result of vascular endothelial growth factor (VEGF) release into the vitreous cavity as a response to ischemia. Furthermore, VEGF increases vessel permeability leading to deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Based on that the differentiated retinoblastoma cells are mostly photoreceptors [32], our result provides that anti-VEGF therapies would affect to the maintenance or function of photoreceptors in mature retina, which is supported by a recent report that the neutralization of endogenous VEGF leads to unexpected neural toxicity [29]. Therefore, regardless of recent reports to demonstrate few clinically relevant ocular side effect [27], [28], pros and cons of anti-VEGF treatment should be carefully scrutinized.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Based on that the differentiated retinoblastoma cells are mostly photoreceptors [32], our result provides that anti-VEGF therapies would affect to the maintenance or function of photoreceptors in mature retina, which is supported by a recent report that the neutralization of endogenous VEGF leads to unexpected neural toxicity [29]. Therefore, regardless of recent reports to demonstrate few clinically relevant ocular side effect [27], [28], pros and cons of anti-VEGF treatment should be carefully scrutinized.…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, regardless of empirical evidence in clinics, anti-VEGF treatment using bevacizumab has been extensively applied in variable vaso-proliferative retinopathies [12][14]. Some clinical reports have demonstrated that intravitreal bevacizumab would be most effective against angiogenic and edematous ocular diseases [27], [28]. However, because VEGF could play as a neurotrophic and neuroprotective factor in nervous system as well as critical roles in vessels, VEGF inhibition could lead to serious neuroretinal damages [3][7].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have led to the recognition of hyperglycemia, hypertension and dyslipidemia as major risk factors for DR. Consequently, tight glycemic control, blood pressure control and lipid-lowering therapy have shown proven benefits in reducing the incidence and progression of DR.[5] In clinic, laser photocoagulation and vitrectomy remain the two conventional approaches to treat sight-threatening conditions such as macular edema and proliferative DR.[6] Vascular endothelial growth factor (VEGF) blockers (Pegaptanib, Ranibizumab and Bevacizumab) in combination with laser photocoagulation represents an emerging novel therapy to reduce macular edema and induce neovascular regression. [57] In spite of this progress, DR remains a major clinical challenge, and the number of patients keeps growing due to difficulty in achieving tight glycemic control, metabolic memory, unresponsive to the current therapeutic approaches and significant side-effects from therapies. [56810] There is a great need to develop new therapeutic approaches for this devastating disease.…”
Section: Introductionmentioning
confidence: 99%
“…Results of another large randomized control trial demonstrated similar results for ranibizumab in the treatment of DME 4647. Promising results for the treatment of DME have also been reported for the use of bevacizumab in a large retrospective and one smaller prospective study4850 and for pegaptanib in a randomized control trial 51…”
Section: Current Treatments Options For Diabetic Macular Edemamentioning
confidence: 77%